COSMIC‐2 Radio Occultation Constellation: First Results. Issue 4 (13th February 2020) - Schreiner, W.S.; Weiss, J.P.; Anthes, R.A.; Braun, J.; Chu, V.; Fong, J.; Hunt, D.; Kuo, Y.‐H.; Meehan, T.; Serafino, W.; Sjoberg, J.; Sokolovskiy, S.; et al.
Abstract: Initial data from the Formosa Satellite‐7/Constellation Observing System for Meteorology Ionosphere and Climate (FORMOSAT‐7/COSMIC‐2, hereafter C2), a recently launched equatorial constellation of six satellites carrying advanced radio occultation receivers, exhibit high signal‐to‐noise ratio, precision, and accuracy, and the ability to provide high vertical resolution profiles of bending angles and refractivity, which contain information on temperature and water vapor in the challenging tropical atmosphere. After an initial calibration/validation phase, over 100, 000 soundings of bending angles and refractivity that passed quality control in October 2019 are compared with independent data, including radiosondes, model forecasts, and analyses. The comparisons show that C2 data meet expectations of high accuracy, precision, and capability to detect superrefraction. When fully operational, the C2 satellites are expected to produce ~5, 000 soundings per day, providing freely available observations that will enable improved forecasts of weather, including tropical cyclones, and weather, space weather, and climate research. Plain Language Summary: This paper describes an initial quality assessment of satellite observations from a recently launched (25 June 2019) constellation of six satellites that orbit Earth over the tropics. The approximately 5, 000 vertical profiles per day, obtained using a relatively new technique called radio occultation, provide information of unprecedented quality on the temperature and water vapor in the tropics. These observations, which are freely available to forecasters and researchers worldwide, will be useful in improving forecasts of weather, including tropical cyclones, and supporting weather and climate research. Key Points: First operational tropical constellation of radio occultation (RO) satellites is collecting atmospheric bending angles and refractivity profiles of unprecedented quality Six advanced Global Navigation Satellite System (GNSS) RO receivers provide up to 5, 000 high signal‐to‐noise ratio (SNR) profiles per day in the tropics First publicly available RO data from GLONASS (GLObal Navigation Satellite System)